Analisis Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pelanggan di Resto Kita Karawang - Dini Oktaviani; Puji Isyanto; Neni Sumarni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of the research was to obtain an in-depth understanding of the influence of service quality and product quality on the level of customer satisfaction at Resto Kita Karawang. This research uses quantitative methods in its research methodology. Using a questionnaire to collect and analyze data from customers who meet the criteria of having made at least two purchases from Resto Kita Karawang. And involving 96 respondents as research samples selected through a purposive sampling method. The analysis was carried out using multiple linear regression analysis. The results of the research show that customer satisfaction is influenced by service quality and product quality at Resto Kita Karawang. These results can be understood from the calculations that have been carried out which show that the variables of service quality and product quality have great value in customer satisfaction. Resto Kita Karawang needs to focus on improving its quality and maintaining this quality to strengthen customer satisfaction. There are implications that by always being consistent in maintaining customer satisfaction and always maintaining quality, it can create a high sense of loyalty.